Fiqh Awlawiyyat Dalam Fatwa Berkaitan Covid-19: Analisis Fatwa Terpilih - Abdul Manan Ismail; Mushaddad Hasbullah; Irwan Mohd Subri; Lukman Abdul Mutalib; Mohd Soberi Awang; Shahirah Hafiz Mohd Tahir Naeem (Usuli Faqih Research Centre PLT, 2024)
Indexed by MyCite